Molecular markers associated with resistance to commonly used antimalarial drugs among Plasmodium falciparum isolates from a malaria-endemic area in Taiz governorate—Yemen during the transmission season - Alareqi, L.M.Q.; Mahdy, M.A.K.; Lau, Y.L.; Fong, M.Y.; Abdul-Ghani, R. (Elsevier, 2016)
Since 2005, artesunate (AS) plus sulfadoxine/pyrimethamine (SP) combination has been adopted as the first-line treatment for uncomplicated malaria in Yemen in response to the high level of Plasmodium falciparum resistance to chloroquine (CQ). Therefore, the aim of the present study was to determine the frequency distribution of molecular markers associated with resistance to CQ and AS plus SP combination among P. falciparum isolates from a malaria-endemic area in Taiz governorate, Yemen. Fifty P. falciparum isolates were collected during a cross-sectional study in Mawza district, Taiz, in the period from October 2013 to April 2014. The isolates were investigated for drug resistance-associated molecular markers in five genes, including P. falciparum CQ resistance transporter (pfcrt) 76T and P. falciparum multidrug resistance 1 (pfmdr1) 86Y as markers of resistance to CQ, mutations in the Kelch 13 (K13) propeller domain for resistance to AS, and P. falciparum dihydrofolate reductase (pfdhfr) and P. falciparum dihydropteroate synthase (pfdhps) genes for resistance to SP. Nested polymerase chain reaction was used to amplify target genes in DNA extracts of the isolates followed by restriction fragment length polymorphism for detecting 76T and 86Y mutations in pfcrt and pfmdr1, respectively, and by DNA sequencing for detecting mutations in K13, pfdhfr and pfdhps. All the investigated isolates from Mawza district were harboring the pfcrt 76T mutant and the pfmdr1 N86 wild-type alleles. The pfdhfr 51I/108 N double mutant allele was found in 2.2% (1/45) of the isolates; however, no mutations were detected at codons 436, 437, 540, 581 and 613 of pfdhps. All P. falciparum isolates that were successfully sequenced (n = 47) showed the K13 Y493, R539, I543 and C580 wild-type alleles. In conclusion, the pfcrt 76T mutant allele is fixed in the study area about six years after the official withdrawal of CQ, possibly indicating its over-the-counter availability and continued use as a self-medication in the study area. However, the almost predominant wild-type alleles of the genes associated with resistance to AS and SP among P. falciparum isolates in the present study indicates the sustained efficacy of the currently adopted first-line treatment of AS plus SP in the study area.